2018
DOI: 10.1039/c6fo01174h
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of plant food supplements in the Netherlands

Abstract: The use of food supplements containing herbs or other botanical ingredients (plant food supplements, PFS) is on the rise. In some cases, PFS can contain compounds that are toxic and may pose a health risk. To assess the potential health risks, information on the consumption of PFS is required, however, this was lacking for the Netherlands. In the current study, the consumption of PFS was investigated for several subgroups in the Dutch population, including children. Data from the Dutch National Food Consumptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Botanical supplements are a major NVNM supplement used around the world [ 20 , 30 , 39 , 40 ]. Echinacea is the most common botanical supplement in Western countries [ 20 , 30 , 39 ]. Echinacea , also known as coneflower, of family Astraceae , is endemic to North America and is a known immunostimulant and widely used as a dietary supplement in North America and Europe [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Botanical supplements are a major NVNM supplement used around the world [ 20 , 30 , 39 , 40 ]. Echinacea is the most common botanical supplement in Western countries [ 20 , 30 , 39 ]. Echinacea , also known as coneflower, of family Astraceae , is endemic to North America and is a known immunostimulant and widely used as a dietary supplement in North America and Europe [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Botanical supplements are a major NVNM supplement used around the world [20,30,39,40]. Echinacea is the most common botanical supplement in Western countries [20,30,39].…”
Section: Discussionmentioning
confidence: 99%
“…The food supplement market emerged from the global recession relatively unscathed [1]; in 2015 it was worth €7.2 billon to the European economy, a figure expected to grow to €7.9 billion by 2020 [2]. Food Supplements based on botanical ingredients like echinacea, valerian or gingko, comprise its second largest segment after vitamins and minerals and are typically used by around 20% of consumers in developed nations [3, 4].…”
Section: Introductionmentioning
confidence: 99%
“…The ten species mentioned most often (by at least 102 participants or 3.5%) were ginkgo, evening primrose, artichoke, ginseng, aloe vera, fennel, valerian, soybean, lemon balm, and echinacea. A more recent survey of plant food supplement use (excluding herbal medicines), among 1230 participants, was published by Jeurissen et al [ 9 ]. They found that products of a great variety of species (>100) were used with echinacea (14.2%), ginkgo, cranberry, ginseng, algae (such as spirulina and chlorella), citrus bioflavonoids, grape seeds, valerian, rose hip, and garlic (4.7%) being the ten most frequently reported.…”
Section: Assessment Of Herbal Drugs and Their Interactionsmentioning
confidence: 99%
“…Surveys among pediatric, adult, and elderly patients in several countries reveal that between 15 and 45% of patients use herbal products for healthcare purposes, besides prescribed medicine [ 2 , 3 , 4 , 5 , 6 ]. The use of complementary herbal medicines and food supplements is particularly frequent among women and older people [ 7 , 8 , 9 ]. Surveys indicate that patients with chronic diseases use more supplements [ 8 ].…”
Section: Introductionmentioning
confidence: 99%